Faktor Internal Yang Berhubungan Dengan Kualitas Hidup Penderita Diabetes Melitus - Mahmadiariska, Theresia Daniela Ody; Debora, Oda; Putri, Maria Prieska; Ariesti, Ellia (Universitas Tribhuwana Tunggadewi, 2024)
Type 2 Diabetes Mellitus is a chronic disease that can significantly impair the quality of life. Individuals with this condition often experience physical and mental disturbances, affecting their activities, medical therapy, rest, and pain perception, all of which are dimensions of quality of life. Factors that can influence the quality of life of individuals with Diabetes Mellitus include their level of knowledge about the disease, economic status, and duration of illness. This study aims to investigate the internal factors related to the quality of life of individuals with Diabetes Mellitus at the Janti Public Health Center in Malang. The research design employed is descriptive correlational with a cross-sectional approach. The study sample consists of 93 respondents selected using purposive sampling. Data analysis was conducted using ANOVA, with the instruments used are the World Health Organization Quality of Life (WHOQOL)-BREF and the Diabetes Knowledge Questionnaire (DKQ24). The analysis results indicate a significant correlation between knowledge (p=0.003 0.05), economic status (p=0.007 0.05), duration of illness (p=0.008 0.05) to the quality of life. The most influential factor is the duration of illness, as respondents who have been suffering for more than 10 years tend to feel that their activities are disrupted by Diabetes Mellitus and may develop complications in other organs, significantly affecting their quality of life. This study can serve as a reference for further scholarly development, thereby facilitating ongoing exploration of factors associated with quality of life.